Latent tuberculosis screening and treatment in HIV: highly acceptable in a prospective cohort study. Issue 2 (25th April 2022) - White, Helena A.; Okhai, Hajra; Sahota, Amandip; Maltby, John; Stephenson, Iain; Patel, Hemu; Hefford, Philip M.; Wiselka, Martin J.; Pareek, Manish
Background: People living with HIV (PLWH) are at increased risk of re-activation of latent tuberculosis infection (LTBI). Although UK and international guidelines identify this group as a priority for LTBI screening and treatment, data on attitudes of PLWH to this policy recommendation are lacking. Methods: A five-point, Likert-style questionnaire was administered to PLWH to assess views and intentions towards accepting LTBI screening and treatment. Subsequent interferon-γ release assay (IGRA) testing was offered, and chemoprophylaxis if required. Influencing demographic and psychological associations with planned, and actual, testing and treatment uptake were assessed using multivariable logistic regression. Results: 444 out of 716 (62%) patients responded. 417 out of 437 (95.4%) expressed intention to accept LTBI testing. The only significant association was the perceived importance of testing to the individual (adjusted odds ratio (aOR) 8.98, 95% CI 2.55–31.67). 390 out of 393 (99.2%) accepted appropriate IGRA screening; 41 out of 390 (10.5%) were positive. 397 out of 431 (92.1%) expressed intention to accept chemoprophylaxis, associated with perceived importance of treatment (aOR 3.52, 95% CI 1.46–8.51), a desire to have treatment for LTBI (aOR 1.77, 95% CI 0.99–3.15) and confidence in taking treatment (aOR 3.77, 95% CI 1.84–7.72). Of those offered chemoprophylaxis, 36 out of 37 (97.3%) accepted and 34 out of 36 (94.4%) completed treatment. There were no correlates with actual screening acceptance. Conclusions: LTBI is common amongst PLWH, highlighting the importance of robust screening and treatment programmes. This study shows that screening and treatment for LTBI is highly acceptable to PLWH and provides strong, objective evidence for policy-makers developing guidelines in this cohort. This detailed exploration of the views of people living with HIV in the UK through a prospective questionnaire cohort study is the first of its kind in the published literature, and shows that latent TB screening and treatment is overwhelmingly supported https://bit.ly/3HmhmRy